1992
DOI: 10.1029/92gl02378
|View full text |Cite
|
Sign up to set email alerts
|

ionospheric modification with a VLF transmitter

Abstract: Detectable heating of the nighttime D region by a 28.5 kHz signal is observed in 16 out of 144 cases with events occurring under conditions of moderate to low D region electron densities as represented by the unperturbed VLF signal levels. Three dimensional modeling of the effects of NAU heating on a probe VLF signal predicts values in general agreement with observations and suggests that maximum effects should occur under tenuous D region conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 8 publications
1
27
0
Order By: Relevance
“…It is suggested that the cross modulation is due to heating of the D region just above the transmitter which changes the electron collision frequency and thus the electrical conductivity. The modified electron collision frequency is given by (Maslin, 1974;Inan et al, 1992) u0 -2u0 [7 v= ~-+ + '~' -,…”
Section: Vlf Cross Modulationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested that the cross modulation is due to heating of the D region just above the transmitter which changes the electron collision frequency and thus the electrical conductivity. The modified electron collision frequency is given by (Maslin, 1974;Inan et al, 1992) u0 -2u0 [7 v= ~-+ + '~' -,…”
Section: Vlf Cross Modulationmentioning
confidence: 99%
“…Inan et al (1992) and theoretically investigated the modification of the electron density in the nighttime D region. The equations of their model are the continuity equations under steady-state conditions (i.e., Equation (5) without the term due to the loss of particles by movement) for four species: the electron density, the positive ion density, the negative ion density, and the positive water cluster ion density.…”
Section: Vlf Cross Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Associated with these theoretical models, many researches about lower ionospheric heating by very low frequency (VLF) waves were published [ Inan et al ., ; Rodriguez et al ., ; Rodriguez , ; Marshall , ]. Inan et al .…”
Section: Introductionmentioning
confidence: 98%
“…Inan et al . [] created a three‐dimensional model about the heating effect on the nighttime D region through a probe with VLF signal. They showed that the theoretical predicted values were in general agreement with the observations and the maximum heating effects occurred under tenuous D region conditions.…”
Section: Introductionmentioning
confidence: 99%